PENGOLAHAN HASIL MAPPING MENGGUNAKAN APLIKASI AGISOFT UNTUK MENENTUKAN DIGITAL ELEVATION MODEL (DEM) - Andria Kurniawan (Jurnal Vokasi Teknik Sipil, 2024)
Methods for carrying out mapping activities are also developing along with the increasing need for geospatial data in various fields in a region. In using UAV technology, it is also necessary to help the use of Ground Control Points as a coordinate point binder so that aerial photography products have high accuracy. The purpose of the discussion is to find out how to take mapping data using RTK drone technology and process mapping data using the Agisoft application. The methodology used to obtain these data was carried out by literature study, observation study, interview, and consultation with the main contractor. In the process of taking and processing mapping data on the project carried out at Dhoho International Airport Kediri. At the time of the implementation of mapping using RTK drones, the determination and distribution of GCPs began, followed by processing stages starting from the filltering stage to orthophoto. After that, the results of the aerial photo data processing will be used as contours and the DEN will also be used as a map as a basis for cut and fill calculations.